Characteristics of Cryptoasset-Related Crimes and Convergence-Based Law Enforcement Policies - Setiawan, Peter Jeremiah; Jennifer, Jennifer (Faculty of Law, Universitas Jenderal Soedirman, 2023)
Crimes related to cryptoassets that develop in a complex manner give rise to distinctive characteristics and require a convergence-based countermeasure that is not only responsive but also anticipatory and futuristic. This article is examined from normative juridical research with a case and conceptual approach and aims to study the characteristics of crimes related to cryptoassets and how to formulate convergence-based law enforcement policies in Indonesia. This crime has the characteristics of convergence between financial crimes and cybercrime, occurs in cyberspace and is carried out by actors who are described not only from cryptoasset transaction actors, but also third parties who provide services related to cryptoasset transactions. Law enforcement policies in tackling these crimes must have a convergence load with various technological innovations, including data storage and crime investigation using a blockchain system, including verification of cryptoassets using a chain of custody architecture and confiscation and confiscation of cryptoassets related to crime. The formation of convergence-based criminal policies cannot be separated from awareness and continuous efforts to develop the quality of human resources in digital literacy. This quality is not only described in the mastery of technology alone but also in ethical behavior. This digital ethics-based legal culture should not only be aimed at the general public as a norm target (norm address), but also for law enforcement officers (rechtshandhaving).